Analysis of International Competitive Strategy of BHS Sarong PT Behaestex - Ilham, Rachmad; Sudarmiatin, Sudarmiatin; Handayati, Puji (International Journal of Science, Technology & Management, 2025)
This study aims to determine the competitive strategy analysis of PT. Behaestex and recommends a competitive strategy analysis of PT. Behaestex that must be developed in order to increase business competitiveness. Data collection uses document analysis to understand holistically about the unique phenomena in the research object of PT. Behaestex. The analysis method used is qualitative descriptive case study. SWOT analysis shows that the company needs to increase the strengths of the company to be known by consumers and be able to compete with similar companies, especially globally or internationally. Strategies that can be concluded from the SWOT matrix include: SO strategy, namely using the company's strengths in the field of production to control international market share, WO strategy, namely forming a marketing team to expand international marketing reach, ST strategy, namely by diversifying products according to international consumer demand, and WT strategy, namely introducing products to all employees and maximizing production effectiveness.